2017
DOI: 10.1038/srep46408
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal IgA and IFN-γ+ CD8 T cell immunity are important in the efficacy of live Salmonella enteria serovar Choleraesuis vaccines

Abstract: Salmonellosis, a disease caused by non-typhoidal Salmonella strains which can be transmitted from swine to humans, is one of the leading public health problems around the world. Paratyphoid of swine is controlled by vaccinating swine with Salmonella enterica serovar Choleraesuis (S. Choleraesuis) live vaccine strain C500 in China. Although the vaccine has good prophylactic efficacy, the mechanism of immunogenicity is unclear. Using a C500-derived paratyphoid thermo-stable live vaccine (PTSL vaccine), we demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Nevertheless, the presence of O-antigen may be essential for the efficacy of inactivated Salmonella vaccines, as the sera induced by inactivated rough strain immunization were not able to kill Salmonella (Rondini et al, 2013 ). Immunization with live Salmonella vaccines elicits robust humoral and T cell-mediated immune responses, both of which are required for preventing Salmonella infection (Wahid et al, 2015 ; Zhu et al, 2017 ). In addition to the protective antigen O-polysaccharide, specific immune responses stimulated by other Salmonella antigens, such as flagellin proteins and OMPs are strongly associated with protection against Salmonella infection (Mastroeni and Menager, 2003 ; Bergman et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the presence of O-antigen may be essential for the efficacy of inactivated Salmonella vaccines, as the sera induced by inactivated rough strain immunization were not able to kill Salmonella (Rondini et al, 2013 ). Immunization with live Salmonella vaccines elicits robust humoral and T cell-mediated immune responses, both of which are required for preventing Salmonella infection (Wahid et al, 2015 ; Zhu et al, 2017 ). In addition to the protective antigen O-polysaccharide, specific immune responses stimulated by other Salmonella antigens, such as flagellin proteins and OMPs are strongly associated with protection against Salmonella infection (Mastroeni and Menager, 2003 ; Bergman et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of RNA transcript levels by qPCR showed that all mutant strains induced less inflammatory cytokine production than the wild-type strain C78-3 at both 6 h (a and c) and 12 h (b and d) post-infection. &, P < 0.05, C78-3 ΔP fur88 TT araC P BAD fur compared to C78-3; #, P < 0.05, ##, P < 0.01, rSC0012(pS-SaoA) compared to rSC0011(pS-SaoA); *, P <0.05, **, P < 0.01, strains with ΔP fur88 TT araC P BAD fur mutation compared to C78-3 stimulate higher heterologous protection than a Δrfc strain without RDAS [26]. Thus, in addition to colonization level, other determining factors may exist to induce the enhanced protection achieved by regulated delayed attenuation.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are do exist high levels of colonization but low immunogenicity. A strain with the regulated delayed rfc mutation exhibits superior colonization and yet does not stimulate higher heterologous protection than a Δrfc strain without RDAS [36]. humoral responses than rSC0011 in mice.…”
Section: Discussionmentioning
confidence: 99%